Subretinal suspensions of hiPSC-derived retinal pigment epithelium cells form functional monolayers in NOD-SCID mice facilitating treatment of advanced retinal diseases - Xiaojing Song; Guanjie Gao; Ke Ye; Ping Xu; Yuan Wang; Suai Zhang; Dandan Zheng; Jian Ge; Xiufeng Zhong (Regenerative Therapy)
Introduction: Transplantation of human induced pluripotent stem cells derived retinal pigment epithelium (hiPSC-RPE) is regarded as one of the most promising strategies for advanced retinal degenerative diseases leading to blindness, such as age-related macular degeneration. Despite its therapeutic potential, this approach is encumbered by critical challenges, notably the survival of donor RPE cells post-transplantation and the successful reconstruction of a functional RPE layer. Methods: With our previously reported strategy, abundant hiPSC-RPEs were generated from human induced pluripotent stem cells. These cells were characterized in vitro by morphology, marker expression and function. Further, hiPSC-RPE cell suspensions were injected into the eyes of NOD-SCID mice. Animals were monitored by optical coherence tomography screening and color fundus imaging to evaluate the survival of hiPSC-RPEs. Polarity, maturity, integration and phagocytosis of hiPSC-RPEs were analyzed histologically. Results: hiPSC-RPE cells exhibited a cobblestone morphology with abundant microvilli and tight junctions, expressed RPE specific molecular markers, and possessed ability to phagocytize photoreceptor outer segments (POS), thereby resembling the characteristics of the native human RPE cells. Following transplantation into NOD-SCID mice, the cells survived for the 8-week testing period and formed a highly organized monolayer in regions with an intact Bruch's membrane (BM) in the host retina. The reconstructed RPE layer expressed both human-specific and RPE-specific markers with POS phagocytic function. No severe adverse effects, such as malignant tumors or infections, were observed. Conclusions: These findings demonstrate that hiPSC-RPE suspensions can survive and form RPE monolayers with morphological and functional features analogous to those of native human RPE cells in the host retina with a healthy BM. Our study may facilitate the development of cell-based therapies for treatment of advanced retinal degenerations.